2021
DOI: 10.3126/jucms.v9i01.37859
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Profile and Colonoscopic Findings in Patients Presented with Lower Gastrointestinal Bleeding in UCMS

Abstract: INTRODUCTION The lower gastrointestinal bleeding (LGIB) is an alarming symptom and common disease with annual admission of 0.15% with mortality rate of 5-10%. LGIB is caused by neoplastic and non-neoplastic lesions. For accurate diagnosis of various colorectal lesions, colonoscopy is gold standard, convenient and cost effective procedure. It is the investigation of choice in LGIB and helps in early diagnosis of colorectal carcinoma. This study was aimed to scrutinize the clinical and colonoscopic finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 2 publications
1
6
1
Order By: Relevance
“…12 The mean age of presentation of LGIB was 59± 16.9 years in the western country. 13 7,14,15 Similar findings were observed in our neighbouring country. 16,17 This reflects the possibility of similar environmental risk factors and patterns of LGI disease prevailing within the country.…”
Section: Discussionsupporting
confidence: 89%
“…12 The mean age of presentation of LGIB was 59± 16.9 years in the western country. 13 7,14,15 Similar findings were observed in our neighbouring country. 16,17 This reflects the possibility of similar environmental risk factors and patterns of LGI disease prevailing within the country.…”
Section: Discussionsupporting
confidence: 89%
“…Also, Shahi et al (6) found that colonoscopy detected abnormality in 73.8% cases. The common nonneoplastic were hemorrhoids and non-specific colitis (14.5% each) followed by 12.5% of neoplastic cases.…”
Section: Discussionmentioning
confidence: 96%
“…Regarding special habits, 4.6% were smokers, 2.3% were drinkink alcohol, and 6.2% were taking illicit drugs. Shahi et al (6) revealed total 88 patients were included in the study. The mean age of their patients was 48 ±17 years with age range from 17-81 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations